2019
DOI: 10.9770/jesi.2019.7.2(15)
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of barriers faced by female graduate entrepreneurs in Bangladesh

Abstract: This study explores and examines barriers faced by female graduate entrepreneurs founding and growing SMEs in Bangladesh. It particularly seeks to address the current gap in the literature on the barriers faced specifically by female graduate entrepreneurs in Bangladesh, and is among the first of its kind. We conducted 12 semi-structured interviews including 6 graduate female entrepreneurs of SMEs and 6 scholars in entrepreneurship in Dhaka, Bangladesh, and found that educated, graduate, females faced more bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 15 publications
4
39
0
Order By: Relevance
“…Rural women in agriculture production are still under this kind of socioeconomic constraint [15]. Even educated female entrepreneurs are not out of these problems in Bangladesh [16]. Despite these challenging situations, women are providing valuable contributions to national assets.…”
Section: Role Of Bangladeshi Women In Diverse Agriculturalmentioning
confidence: 99%
“…Rural women in agriculture production are still under this kind of socioeconomic constraint [15]. Even educated female entrepreneurs are not out of these problems in Bangladesh [16]. Despite these challenging situations, women are providing valuable contributions to national assets.…”
Section: Role Of Bangladeshi Women In Diverse Agriculturalmentioning
confidence: 99%
“…For example, Kleibert (2015) reported how large foreign investors employed university graduates in low skill work in the Philippines. Islam et al (2019) reported in Bangladesh how gender relationships made it difficult for female graduate entrepreneurs to put their skills into action. These works suggest that the mismatch between graduates and employment and productivity demands are not just about what is or is not learned in TE, but rather a complex relationship associated with the strategies of firms and existing social relationships, of gender or ethnicity, which come to be reproduced in a misaligned or negative direction of change between TE, economic growth and equity.…”
Section: Tertiary Education and The Implementation Of The Sdgs: Undermentioning
confidence: 99%
“…Economic growth in a country is positively associated with the level of female entrepreneurial activity (Raghunandan, 2018). Unfortunately, the potential for graduate female-owned SMEs to contribute to national GDP has been limited (Islam, Jantan, Hunt, Rahman, & Abdullah, 2019). Empowering women with more education may lead to achieve their goals (Weber and Ahmed, 2014), and sustainable livelihood (Ferdousi & Mahmud, 2019), which are mandatory pre-requisites for sustainable development (Rahman & Bari, 2016), and for a better future (Li, Ahmed, & Qalati, 2019).…”
Section: Sustainable Development Agenda and Entrepreneurshipmentioning
confidence: 99%
“…Women entrepreneurship is vital for economic growth (Shoma, 2019) of a country. In Bangladesh, women represent more than 40% of labor-force and lead to 'private industry revolution' (Islam, Jantan, Hunt, Rahman, & Abdullah, 2019) , the gender gap prevails in ownership of the Small and Medium Enterprises (SMEs) (92.6% for males versus 7.4% for females) (Chowdhury, Mintoo, Chowdhury, & Ahmed, 2010) (Kabeer, 2012), women-owned firms (3-4% of total business enterprises) (Ahmed M. U., 2014) and among micro-merchants (94,800 out of 1.3 million) (UNCDF, 2019). The graduate females despite being 2.5 times higher than their male-counterparts, often reluctant to join the labor-force for various social, cultural and workplace-related issues (The Daily Star, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation